Lectotypification of the names of all accepted species of Agenium (Poaceae, Andropogoneae) - Costa, Mitchel Iago Alves; Zuloaga, Fernando Omar; Welker, Cassiano A. Dorneles (Phytotaxa, 2019)
Agenium is a taxonomically complicated and poorly known grass genus, comprising four species from South America. In this paper, lectotypes are designated for the names of all accepted species of Agenium (A. goyazense, A. leptocladum, A. majus, and A. villosum), and images of the chosen lectotypes are presented.